it is 1
no x would be 0.5 because two times 0.5 is 1 ( 2x ) and then add 7 equals 8 ( plus seven equals 8 )
2x + 3y = 5 So 3y = -2x + 5 or y = -2/3x + 5 Now that the equation is in standard form, you just read the slope off as the coefficient of x, ie slope = -2/3
2x+3=9 2x=9-3 2x=6 2x/2=6/2 X=3
It is: y = 2x-3
In standard form it is 4x - 4y = 6 or 2x - 2y = 3
It depends on what you are calling "standard form". 2x = 7 can be solved, but it is a standard form of an algebraic equation.
y + 4 = 2x −1
2x+12-3x = 5 2x-3x = 5-12 x = -7
The slope is the coefficient of x in the standard form and so it is 2.
y=2x y-2x=0 or 2x-y=0
it equals 13X.